Method for in-situ construction of MOF on surface of cellulose fiber fabric through one-step method
By impregnating solutions of metal ions, polyphenols and phosphorus-containing flame retardant on cellulose fiber fabrics in one-step, and baking them to form MOFs, the problems of low bond fastness and insufficient heat resistance in the prior art are solved, and the problem of low bonding fastness and insufficient heat resistance in the prior art is realized Efficient and stable MOF construction.
Patent Information
- Application Number
- CN202411631290.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The prior art When constructing MOF on cellulose fiber fabrics, the bond fastness is low, moisture permeability is damaged, and the product lacks heat resistance and superhydrophobicity, and cannot maintain structural stability in a humid or acid-base environment.
Using a one-step method, the cellulose fiber fabric is immersed in a solution containing both metal ions, polyphenols and phosphorus-containing flame retardant, remove excess water on the surface and bake it, so that the metal ions and polyphenols form coordination bonds and form self-assembly. MOF.
The good combination of MOF and cellulose fiber fabric is achieved, the moisture permeability of the fabric is maintained, and the heat resistance and superhydrophobicity are imparted, which enhances the stability and adhesion of MOF.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and particularly relates to a one-step method for in-situ constructing MOF on the surface of cellulose fiber fabric. Background Art
[0002] Metal-organic frameworks (MOFs) are porous materials formed by metal ions or clusters and organic ligands through coordination bonds. They have a highly ordered structure and a large specific surface area. The pore size can be precisely controlled by adjusting their composition. They are widely used in gas storage, catalysis, sensing, and drug delivery, and have good chemical and thermal stability. Cellulose fiber is a natural polymer material with excellent mechanical strength, biocompatibility, and degradability. The hydroxyl groups in cellulose molecules can combine with metal ions or ligands in MOF to form a stable composite material.
[0003] Constructing MOF on cellulose fiber fabrics can bring innovative applications to multiple fields, mainly involving the following aspects: ① By combining MOF with cellulose fibers, the adsorption, filtration and catalytic capabilities of the fibers can be improved, especially in the fields of water treatment and gas separation, the efficiency of the composite material is significantly improved; ② In industrial catalysis, MOF can be used as a high-efficiency catalyst or catalyst carrier, and cellulose fiber as a substrate can provide good dispersibility and processability, making the catalytic process more efficient; ③ Due to its adjustable pore size and biocompatibility, MOF has shown potential in drug delivery and medical imaging. Combining it with cellulose fibers can improve drug loading capacity and achieve controlled release; ④ The surface functionalization of MOF can form various types of chemical bonds with the hydroxyl groups of cellulose to produce different surface activities, thereby adjusting the function of the composite material according to needs.
[0004] There are two problems that are difficult to solve simultaneously when constructing MOF on cellulose fiber fabrics:
[0005] (1) Most existing technologies prepare MOF first and then transfer MOF to the surface of cellulose fiber fabric through other processing methods. The bonding strength between MOF and cellulose fiber fabric is low, and the original moisture permeability and air permeability of the fabric will be destroyed.
[0006] (2) The product does not have heat resistance and super hydrophobicity, and cannot prevent the structural degradation of MOF in a humid or acidic or alkaline environment. For example, patent CN116043551B discloses a cotton fabric with antiviral biological activity and a preparation method thereof. First, the fabric is impregnated with an L-cysteine solution and then heated for esterification to connect the L-cysteine molecules to the fiber surface; the esterified fabric is again immersed in the L-cysteine solution, and a copper ion solution is added dropwise under stirring to induce the formation of an L-cysteine / copper ion MOF structure on the cotton fiber surface. The product prepared by this patent does not have heat resistance and super hydrophobicity.
[0007] Therefore, it is necessary to propose a new method to in situ construct MOF on the surface of cellulose fiber fabrics to solve the above problems. Summary of the invention
[0008] The purpose of the present invention is to solve the above problems and provide a one-step method for in-situ constructing MOF on the surface of cellulose fiber fabric.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric, wherein the cellulose fiber fabric is immersed in a solution containing metal ions, polyphenols (such as caffeic acid, gallic acid, chlorogenic acid, dopamine, etc.) and a phosphorus-containing flame retardant, and then excess water on the surface of the cellulose fiber fabric is removed and baked, so that the metal ions and the polyphenols and the phosphorus-containing flame retardant form coordination bonds and self-assemble to form MOF, thereby obtaining a cellulose fiber fabric containing MOF on the surface;
[0011] Phosphorus-containing flame retardants have amino and / or hydroxyl groups, such as tetrakishydroxymethylphosphonium chloride, ammonium polyphosphate, phytic acid, phosphonic acid derivatives with amino and / or hydroxyl groups, etc.
[0012] In the prior art, polyphenols are often simply used as ligands when preparing MOFs. The present invention, for the first time, utilizes the property that polyphenols can be oxidized into polymers by certain metal ions under acidic conditions, and utilizes metal ions to oxidize polyphenols to form polyphenol oligomers with a certain viscosity, thereby helping metal ions and phosphorus-containing flame retardants to better adhere to the fiber surface, providing a good foundation for the subsequent generation of MOFs, and also helping MOF to adhere to the fabric surface, so that MOF has good bonding strength and will not damage the original moisture permeability and air permeability of the fabric.
[0013] The metal ion is Cu2+, and the pH value of the solution containing the metal ion, polyphenol and phosphorus-containing flame retardant is 4-6; within this pH range, Cu2+ remains dissolved and can effectively catalyze the oxidation reaction of polyphenol to generate quinone compounds, and then continue the polymerization reaction; Cu2+ oxidizes polyphenol through redox cycle (Cu2+ / Cu+), if the pH value is greater than 6, Cu2+ will combine with OH- to form Cu(OH)2 precipitation and lose catalytic activity, if the pH value is less than 4, although Cu2+ can remain dissolved, the oxidation reaction rate of polyphenol may slow down, because the excessive proton concentration may inhibit the oxidation of polyphenol;
[0014] Alternatively, the metal ion is Fe3+, and the pH value of the solution containing the metal ion, the polyphenol and the phosphorus-containing flame retardant is 2-4; within this pH range, Fe3+ can effectively catalyze the oxidation reaction of the polyphenol and promote the polymerization reaction of the polyphenol through redox cycle (Fe3+ / Fe2+), if the pH value is greater than 4, Fe3+ will rapidly hydrolyze to form Fe(OH)3 precipitation, resulting in catalytic failure, if the pH value is less than 2, although Fe3+ remains dissolved, the excessively high proton concentration may reduce the reaction rate and affect the catalytic efficiency;
[0015] In a solution containing metal ions, polyphenols and phosphorus-containing flame retardants, the concentration of metal ions is not less than 0.1 g / L, and the concentration of polyphenols is not less than 1 g / L; if the concentration of metal ions is too low, insufficient metal ions will result in insufficient MOF production; if the concentration of polyphenols is too low, insufficient polyphenols will result in ineffective coordination and unstable MOF structure;
[0016] The impregnation temperature is not less than 40°C; a suitable impregnation temperature can accelerate the oxidative polymerization reaction of polyphenols and facilitate the initial coordination of metal ions and polyphenols. If the impregnation temperature is too low, the rate of adsorption of metal ions, polyphenols and phosphorus-containing flame retardants on the fiber surface will slow down, which may lead to insufficient adsorption and affect the subsequent MOF generation.
[0017] The impregnation time is not less than 20 minutes. The impregnation time must not only ensure that the metal ions, polyphenols and phosphorus-containing flame retardants can be fully adsorbed by the fiber, but also provide sufficient time for the oxidative polymerization reaction of polyphenols. If the impregnation time is too short, the oxidative polymerization process of polyphenols may not be completed, and insufficient oligomers are generated, which makes it difficult for metal ions and flame retardants to evenly adhere to the fiber surface, affecting the uniformity and performance of subsequent MOF.
[0018] The cellulose fiber fabric containing MOF on the surface of the present invention has heat resistance and super hydrophobicity, which makes up for the shortcomings of the prior art. This is because the phosphorus-containing flame retardant has good heat resistance, the water solubility of polyphenols decreases after polymerization or coordination with metal ions, the fabric surface has low surface energy, and the MOF on the fabric surface helps to form roughness.
[0019] As the preferred technical solution:
[0020] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric as described above, wherein the concentration of metal ions in the solution containing metal ions, polyphenols and phosphorus-containing flame retardants is not higher than 1.5 g / L, the concentration of polyphenols is not higher than 5 g / L, and the concentration of phosphorus-containing flame retardants is 0.5-3 g / L;
[0021] The concentration of metal ions should not be too high, otherwise it will cause excessive or uneven deposition on the fiber surface, which may affect the feel and softness of the fabric;
[0022] The concentration of polyphenols should not be too high, otherwise it will lead to the formation of too many oligomers, forming a sticky surface layer, affecting the feel of the fabric, and even immersing or encapsulating the generated MOF;
[0023] The concentration of phosphorus-containing flame retardant is 0.5-3g / L, which can ensure that the flame retardant can work together with metal ions and polyphenols to form a stable MOF coating, while giving the fabric good heat resistance and flame retardant properties. It can avoid the failure to fully exert the flame retardant and heat resistant effects due to insufficient flame retardant, and it can also avoid the formation of too thick phosphorus / phosphonate layer on the fabric surface due to excessive flame retardant, which affects the softness and breathability of the fabric and may even cause a decrease in mechanical properties.
[0024] As described above, in the one-step method for in-situ constructing MOF on the surface of cellulose fiber fabric, the solution containing metal ions, polyphenols and phosphorus-containing flame retardants also contains hydrogen peroxide, and the concentration of hydrogen peroxide is not higher than 0.1 g / L. Hydrogen peroxide can promote the rapid oxidation of metal ions and polymerization of polyphenols. The concentration of hydrogen peroxide should not be too high, otherwise it will increase the oxidation risk of fibers and phosphorus-containing flame retardants.
[0025] In the one-step method for in-situ constructing MOF on the surface of cellulose fiber fabric as described above, the mass ratio of cellulose fiber fabric to the solution containing metal ions, polyphenols and phosphorus-containing flame retardant is 1:10-20, so as to ensure that the solution can fully infiltrate the surface of the fabric and evenly distribute the metal ions. Too much water will affect the deposition uniformity of MOF and cause unstable performance. Too little water will affect the reaction environment and make it impossible to fully generate MOF.
[0026] In the one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric as described above, the immersion temperature is not higher than 60°C, so as to avoid the immersion temperature being too high, which will accelerate the oxidation reaction rate of polyphenols and lead to the formation of too many oligomers, affecting the stability and uniformity of the solution.
[0027] In the one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric as described above, the immersion time is no more than 60 minutes. This can avoid the immersion time being too long, which may cause excessive accumulation of oligomers on the fiber surface, resulting in uneven surface, affecting the feel and the formation of MOF, and causing the fabric to absorb too much water, affecting the subsequent drying and baking steps.
[0028] In the one-step method for in-situ constructing MOF on the surface of cellulose fiber fabric as described above, after removing excess moisture from the surface of cellulose fiber fabric, the residual moisture mass in the cellulose fiber fabric is 60-80% of the mass of cellulose fiber fabric, which can avoid uneven chemical reaction due to excessive moisture removal (too little moisture on the fiber surface will lead to uneven distribution on the surface, thereby affecting the reaction efficiency of metal ions, polyphenols and flame retardants. Too dry fibers will cause chemical reactions to occur locally faster or slower, ultimately affecting fabric properties), fiber embrittlement (when cellulose fibers are over-dried, the cellulose structure may shrink and become brittle, which will cause the fabric to lose mechanical strength and elasticity during subsequent processing), and can also avoid reduced reaction efficiency due to insufficient moisture removal (too much residual moisture on the surface will dilute the chemical composition on the surface, reduce the effective concentration of the reactants, and thus delay the reaction), uneven deposition (if there is too much moisture, the deposition of chemicals on the fiber surface will be uneven, which may lead to inconsistent distribution of polyphenols and metal ions, thereby affecting the formation of MOF), and long baking problems (excessive humidity will also increase the time for subsequent drying and baking, increase energy consumption, and even cause thermal damage to the fiber).
[0029] As described above, the one-step method for in situ constructing MOF on the surface of cellulose fiber fabric has a baking temperature of 100-130°C. This can avoid the degradation of cellulose fibers due to excessively high baking temperatures, affecting the mechanical properties of the fabric (such as strength and flexibility), causing the fabric to turn yellow or become brittle, and can also avoid insufficient crystallization of MOF due to excessively low baking temperatures, which in turn leads to unstable MOF structure.
[0030] As described above, the one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric has a baking time of 30-60 minutes. This can avoid the cellulose fibers becoming brittle or hardened due to excessive baking due to too long baking time, affecting the feel and durability of the fabric, and can also avoid the MOF being unable to be completely generated and solidified due to too short baking time, affecting its stability and adhesion on the fiber surface.
[0031] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric as described in any one of the above items, wherein the MOF on the surface of the cellulose fiber fabric containing MOF is a regular cubic structure;
[0032] The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is ≥28%, and the thermal decomposition temperature is 250-320℃, which is more than 10% higher than that of the original fabric. The heat resistance and flame retardancy are excellent. On the one hand, the phosphorus-containing flame retardant has good heat resistance and flame retardancy, and on the other hand, MOF itself also has certain flame retardancy.
[0033] The water contact angle of the cellulose fiber fabric containing MOF on the surface is ≥160°, and the water adhesion value is ≤28.49μN. It has superhydrophobic and self-cleaning properties, which can prevent stains or other reagents from contaminating and destroying the MOF structure. This is because the water solubility of polyphenols decreases after polymerization or coordination with metal ions, the fabric surface has low surface energy, and the MOF on the fabric surface helps to form roughness;
[0034] The moisture permeability of cellulose fiber fabrics containing MOF on the surface (indicates the amount of water vapor passing through a unit area per unit time) is ≥2200g / (m 2 ·day), air permeability (indicates the amount of air passing through a unit area per unit time) ≥ 150m 3 / (m 2 h), good moisture permeability and air permeability, because polyphenol oligomers are at the molecular level, relying on hydrogen bonds to combine MOF and fabric, with a scale within 10nm, and are molecular layer coating;
[0035] The abrasion loss of cellulose fiber fabric containing MOF on the surface is ≤10g / 100cm 2 The wear cycle number is more than 3500 times, the longitudinal tear strength and transverse tear strength are both ≥30N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate is ≤15%, and after 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate is ≤25%. The wear resistance, tear resistance and durability under harsh conditions are excellent. This is because the oligomer formation reaction of polyphenols can not only provide viscosity, but also form a dense cross-linking network to further enhance the mechanical strength of the fiber.
[0036] After 50 washes, the change rate of each index of the cellulose fiber fabric containing MOF on the surface does not exceed 10%. This shows that the bonding strength between MOF and cellulose fiber fabric is high, because polyphenol oligomers can help MOF bond to the fabric surface.
[0037] When synthesizing MOFs on a large scale, in industrial production, the uneven deposition of MOFs on the fiber surface will affect the overall performance of the material, making it unable to achieve the desired functionality. Therefore, how to maintain the uniform distribution of MOFs and the consistency of material properties on a large area of cellulose fiber fabric is also an important problem.
[0038] To solve this problem, the present invention proposes a simple impregnation-baking method. This method not only does not require complex equipment, but is also easy to scale up in industrial production, and is particularly suitable for the treatment of large-area fabrics. Compared with other MOF synthesis processes (such as solvothermal method or vapor deposition method), the impregnation-baking method has the advantages of low temperature, easy operation and low energy consumption, and is very suitable for large-scale production operations in factories.
[0039] In the impregnation-baking method, polyphenols and polyphenols play an important role as chelating agents. They can not only coordinate with metal ions, but also help control the uniform distribution of metal ions and flame retardants on the fiber surface. This chelation ensures the uniform deposition of MOF on the fiber surface, avoiding the problem of local excessive deposition or precipitation, thereby greatly improving the controllability of MOF synthesis and the consistency of materials, especially in terms of uniformity on large-area fabrics.
[0040] In addition, after impregnation, the present invention also removes excess water from the fabric surface by centrifugation or pressing, and controls the moisture content between 60-80%. This step ensures the uniform distribution of chemical components on the fiber surface. The subsequent heating treatment further ensures that the MOF can stably crystallize and evenly deposit on the fiber surface. This heating strategy not only effectively controls the crystallization process of MOF, but also ensures the consistency of material performance during large-scale production.
[0041] Beneficial effects:
[0042] The present invention discloses a one-step in-situ method for constructing MOF on the surface of cellulose fiber fabric. Through the synergistic effect of polyphenols, metal ions and phosphorus-containing flame retardants, not only the synthesis process of MOF is simplified, but also uniform deposition and strong bonding on the fiber surface are achieved. The viscous oligomers generated by polyphenols under catalytic conditions enhance the adhesion of MOF on cellulose, ensure the stability of interface bonding, and at the same time give the material good heat resistance, flame retardancy and weather resistance.
[0043] The one-step method of the present invention for in-situ construction of MOF on the surface of cellulose fiber fabric is simple to operate and easy to mass produce, and is suitable for the functional treatment of large-area textile materials. It overcomes the problems of insufficient interface bonding force and poor environmental stability in traditional MOF processes, and provides an efficient and sustainable solution for improving the functionality of textile materials. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0045] The detection methods of relevant indicators are as follows:
[0046] Limiting oxygen index: GB / T 5454-1997 "Textile combustion performance test oxygen index method";
[0047] Thermal decomposition temperature: GB / T 37631-2019 Test method for thermal decomposition temperature of chemical fibers;
[0048] Water contact angle: GB / T 42694-2023 "Testing and evaluating the anti-wetting performance of textile surfaces - Contact angle and rolling angle method";
[0049] Adhesion to water: The contact angle and the contact line length between the water drop and the fabric surface are measured using GB / T 42694-2023 “Testing and evaluating the anti-wetting performance of textile surfaces - Contact angle and rolling angle method”. Adhesion value F = γ·L·(1+cosθ), where F is the adhesion to water, in μN (micronewton); γ is the surface tension of water, usually 7.28×10 -2 N / m (under standard conditions of 20°C); θ: contact angle of a water drop on the material surface, in degrees (°); L: length of the contact line between the water drop and the fabric surface (μm).
[0050] Water vapor permeability: GB / T 12704.2-2009 "Test method for water vapor permeability of textile fabrics - Part 2: Evaporation method";
[0051] Air permeability: GB / T 5453-1997 "Determination of air permeability of textile fabrics";
[0052] Abrasion loss: GB / T 21196.3-2007 "Textiles - Determination of the abrasion resistance of fabrics by the Martindale method - Part 3: Determination of mass loss";
[0053] Abrasion cycle number: GB / T 21196.2-2007 "Textiles - Determination of the abrasion resistance of fabrics by the Martindale method - Part 2: Determination of specimen damage";
[0054] Longitudinal and transverse tear strength: GB / T 3917.3-2009 "Tear properties of textile fabrics - Part 3: Determination of tear strength of trapezoidal test specimens";
[0055] Strength reduction rate: GB / T 3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking force and elongation at break (strip method)", measure the tensile strength before and after UV aging, and calculate the percentage of strength reduction;
[0056] Tensile strength reduction rate: GB / T 3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking force and elongation at break (strip method)", measure the change in tensile strength before and after treatment in a high temperature and high humidity environment, and calculate the percentage of tensile strength reduction;
[0057] Washing: ISO 105C06 "Colour fastness to washing".
[0058] Example 1
[0059] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is as follows:
[0060] (1) Prepare raw materials:
[0061] water;
[0062] CuSO4;
[0063] Polyphenols: Caffeic acid;
[0064] Phosphorus-containing flame retardant: tetrakishydroxymethylphosphonium chloride;
[0065] Cellulose fiber fabrics: cotton fiber fabrics;
[0066] (2) Prepare the impregnation solution:
[0067] The CuSO4, polyphenol, phosphorus-containing flame retardant and water are uniformly mixed and the pH of the system is adjusted to 4 to obtain an impregnation solution containing metal ions, polyphenol and phosphorus-containing flame retardant;
[0068] In the impregnation solution, the concentration of metal ions is 0.1 g / L, the concentration of polyphenols is 1 g / L, and the concentration of phosphorus-containing flame retardants is 0.5 g / L;
[0069] (3) Soaking and baking:
[0070] The cellulose fiber fabric was immersed in the impregnation solution at 40°C for 25 minutes, and then the excess water on the surface of the cellulose fiber fabric was removed, and the cellulose fiber fabric was baked at 110°C for 40 minutes to obtain a cellulose fiber fabric with MOF on the surface.
[0071] The mass ratio of the cellulose fiber fabric to the impregnation liquid is 1:15, and after removing excess water on the surface of the cellulose fiber fabric, the mass of the residual water in the cellulose fiber fabric is 70% of the mass of the cellulose fiber fabric.
[0072] The MOF of the cellulose fiber fabric containing MOF on the surface finally obtained is a regular cubic structure. The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is 28%, the thermal decomposition temperature is 250°C, the water contact angle is 160°, the water adhesion value is 28.49μN, and the water permeability is 2554g / (m 2 ·day), air permeability is 186m 3 / (m 2 h), the wear loss is 7.9g / 100cm 2 The wear cycle number is 3700, the longitudinal tear strength is 34N, the transverse tear strength is 33N, and the irradiation intensity is 0.35W / m 2After 500 hours of ultraviolet irradiation, the strength decrease rate is 13%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate is 22%. After 50 times of water washing, the change rate of each index does not exceed 10%.
[0073] Comparative Example 1
[0074] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is basically the same as that in Example 1, except that the pH of the system is adjusted to 3 in step (2).
[0075] The resulting cellulose fiber fabric with MOF on its surface has a limiting oxygen index of 27%, a thermal decomposition temperature of 220°C, a water contact angle of 145°, a water adhesion value of 28.96 μN, and a moisture permeability of 2568 g / (m 2 ·day), air permeability is 190m 3 / (m 2 h), the wear loss is 8.3g / 100cm 2 The wear cycle number is 3350, the longitudinal tear strength is 30N, the transverse tear strength is 29N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate is 15%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate is 25%. After 50 times of water washing, the maximum change rate of each index is 12%.
[0076] By comparing Example 1 with Comparative Example 1, it can be seen that the flame retardancy and heat resistance of the fabric of Comparative Example 1 are reduced, the moisture permeability and air permeability are slightly increased, the abrasion resistance is reduced, the tear strength is reduced, and the physical and mechanical properties are reduced after ultraviolet irradiation and high temperature and high humidity treatment. This is because the pH value is less than 4. Although Cu2+ can remain dissolved, the oxidation reaction rate of polyphenols may be slowed down because the excessively high proton concentration may inhibit the oxidation of polyphenols.
[0077] Comparative Example 2
[0078] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is basically the same as Example 1, except that the concentration of polyphenols in step (2) is 0.5 g / L.
[0079] The resulting cellulose fiber fabric with MOF on its surface has a limiting oxygen index of 25%, a thermal decomposition temperature of 200°C, a water contact angle of 123°, a water adhesion value of 29.14 μN, and a water permeability of 2624 g / (m 2 ·day), air permeability is 192m 3 / (m 2 h), abrasion loss is 8.5g / 100cm 2The wear cycle number is 3100, the longitudinal tear strength is 27N, the transverse tear strength is 28N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate was 17%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate was 26%. After 50 times of water washing, the maximum change rate of each index was 14%.
[0080] By comparing Example 1 with Comparative Example 2, it can be seen that the flame retardancy and heat resistance of the fabric of Comparative Example 2 are reduced, the moisture permeability and air permeability are slightly increased, the abrasion resistance is reduced, the tear strength is reduced, and the physical and mechanical properties are reduced after ultraviolet irradiation and high temperature and high humidity treatment. This is because the concentration of polyphenols is too low. Due to insufficient polyphenols, effective coordination cannot be achieved and the MOF structure is unstable.
[0081] Example 2
[0082] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is as follows:
[0083] (1) Prepare raw materials:
[0084] water;
[0085] CuCl2;
[0086] Polyphenols: Gallic acid;
[0087] Phosphorus-containing flame retardant: ammonium polyphosphate, degree of polymerization 10;
[0088] Cellulose fiber fabric: viscose fiber fabric;
[0089] (2) Prepare the impregnation solution:
[0090] The CuCl2, polyphenol, phosphorus-containing flame retardant and water are uniformly mixed and the pH of the system is adjusted to 5 to obtain an impregnation solution containing metal ions, polyphenol and phosphorus-containing flame retardant;
[0091] In the impregnation solution, the concentration of metal ions is 0.5 g / L, the concentration of polyphenols is 2 g / L, and the concentration of phosphorus-containing flame retardants is 1 g / L;
[0092] (3) Soaking and baking:
[0093] The cellulose fiber fabric was immersed in the impregnation solution at 50°C for 40 minutes, and then the excess water on the surface of the cellulose fiber fabric was removed, and the cellulose fiber fabric was baked at 120°C for 45 minutes to obtain the cellulose fiber fabric with MOF on the surface;
[0094] The mass ratio of the cellulose fiber fabric to the impregnation liquid is 1:10, and after removing excess water on the surface of the cellulose fiber fabric, the mass of the residual water in the cellulose fiber fabric is 60% of the mass of the cellulose fiber fabric.
[0095] The MOF of the cellulose fiber fabric containing MOF on the surface finally obtained is a regular cubic structure. The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is 28.4%, the thermal decomposition temperature is 266°C, the water contact angle is 163°, the water adhesion value is 28.35μN, and the water permeability is 2456g / (m 2 ·day), air permeability is 175m 3 / (m 2 h), the wear loss is 7.6g / 100cm 2 The wear cycle number is 4200, the longitudinal tear strength is 35N, the transverse tear strength is 36N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate is 10%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate is 18%. After 50 times of water washing, the change rate of each index does not exceed 10%.
[0096] Example 3
[0097] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is as follows:
[0098] (1) Prepare raw materials:
[0099] water;
[0100] FeCl3;
[0101] Polyphenols: Chlorogenic acid;
[0102] Phosphorus-containing flame retardants: phytic acid;
[0103] Cellulose fiber fabric: ramie fiber fabric;
[0104] (2) Prepare the impregnation solution:
[0105] The FeCl3, polyphenol, phosphorus-containing flame retardant and water are uniformly mixed and the pH of the system is adjusted to 2 to obtain an impregnation solution containing metal ions, polyphenol and phosphorus-containing flame retardant;
[0106] In the impregnation solution, the concentration of metal ions is 0.8 g / L, the concentration of polyphenols is 3 g / L, and the concentration of phosphorus-containing flame retardants is 1.5 g / L;
[0107] (3) Soaking and baking:
[0108] The cellulose fiber fabric was immersed in the impregnation solution at 40°C for 20 minutes, and then the excess water on the surface of the cellulose fiber fabric was removed, and the cellulose fiber fabric was baked at 100°C for 30 minutes to obtain a cellulose fiber fabric with MOF on the surface;
[0109] The mass ratio of the cellulose fiber fabric to the impregnation liquid is 1:20, and after removing excess water on the surface of the cellulose fiber fabric, the mass of the residual water in the cellulose fiber fabric is 80% of the mass of the cellulose fiber fabric.
[0110] The MOF of the cellulose fiber fabric containing MOF on the surface finally obtained is a regular cubic structure. The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is 28.6%, the thermal decomposition temperature is 274°C, the water contact angle is 162°, the water adhesion value is 28.12μN, and the water permeability is 2348g / (m 2 ·day), air permeability is 168m 3 / (m 2 h), the wear loss is 9.6g / 100cm 2 The wear cycle number is 3500, the longitudinal tear strength is 30N, the transverse tear strength is 30N, and the irradiation intensity is 0.35W / m 2 The strength decrease rate is 15% after 500 hours of ultraviolet irradiation. The tensile strength decrease rate is 25% after 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%. After 50 times of water washing, the change rate of each index does not exceed 10%.
[0111] Comparative Example 3
[0112] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is basically the same as that in Example 3, except that the pH of the system is adjusted to 1 in step (2).
[0113] The resulting cellulose fiber fabric with MOF on its surface had a limiting oxygen index of 25.3%, a thermal decomposition temperature of 198°C, a water contact angle of 132°, a water adhesion value of 29.31 μN, and a water permeability of 2421 g / (m 2 ·day), air permeability is 172m 3 / (m 2 h), abrasion loss is 10.2g / 100cm 2 The wear cycle number is 2850, the longitudinal tear strength is 25N, the transverse tear strength is 26N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate was 23%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate was 29%. After 50 times of water washing, the maximum change rate of each index was 18%.
[0114] By comparing Example 3 with Comparative Example 3, it can be seen that the flame retardancy and heat resistance of the fabric of Comparative Example 3 are reduced, the moisture permeability and air permeability are slightly increased, the abrasion resistance is reduced, the tear strength is reduced, and the physical and mechanical properties are reduced after ultraviolet irradiation and high temperature and high humidity treatment. This is because the pH value is less than 2. Although Fe3+ remains dissolved, excessively high proton concentration may reduce the reaction rate and affect the catalytic efficiency.
[0115] Comparative Example 4
[0116] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is basically the same as Example 3, except that the immersion temperature in step (3) is 35°C.
[0117] The resulting cellulose fiber fabric with MOF on its surface had a limiting oxygen index of 26.1%, a thermal decomposition temperature of 206°C, a water contact angle of 135°, a water adhesion value of 28.97 μN, and a moisture permeability of 2384 g / (m 2 ·day), air permeability is 170m 3 / (m 2 h), the wear loss is 9.9g / 100cm 2 The wear cycle number is 3100, the longitudinal tear strength is 27N, the transverse tear strength is 26N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate was 17%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate was 27%. After 50 times of water washing, the maximum change rate of each index was 15%.
[0118] By comparing Example 3 with Comparative Example 4, it can be seen that the flame retardancy and heat resistance of the fabric of Comparative Example 4 are reduced, the moisture permeability and air permeability are slightly increased, the abrasion resistance is reduced, the tear strength is reduced, and the physical and mechanical properties are reduced after ultraviolet irradiation and high temperature and high humidity treatment. This is because the impregnation temperature is too low, and the rate of adsorption of metal ions, polyphenols and phosphorus-containing flame retardants on the fiber surface is slowed down, which may lead to insufficient adsorption and affect the subsequent MOF generation.
[0119] Comparative Example 5
[0120] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is basically the same as Example 3, except that the immersion time in step (3) is 15 minutes.
[0121] The resulting cellulose fiber fabric with MOF on its surface had a limiting oxygen index of 25.9%, a thermal decomposition temperature of 201°C, a water contact angle of 130°, a water adhesion value of 30.01 μN, and a water permeability of 2398 g / (m 2 ·day), air permeability is 171m3 / (m 2 h), the wear loss is 10.1g / 100cm 2 The wear cycle number is 2900, the longitudinal tear strength is 28N, the transverse tear strength is 27N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate was 19%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate was 28%. After 50 times of water washing, the maximum change rate of each index was 16%.
[0122] By comparing Example 3 with Comparative Example 5, it can be seen that the flame retardancy and heat resistance of the fabric of Comparative Example 5 are reduced, the moisture permeability and air permeability are slightly increased, the abrasion resistance is reduced, the tear strength is reduced, and the physical and mechanical properties are reduced after ultraviolet irradiation and high temperature and high humidity treatment. This is because the oxidative polymerization process of polyphenols may not be completed if the immersion time is too short, and the generated oligomers are insufficient, which makes it difficult for metal ions and flame retardants to adhere evenly to the fiber surface, affecting the uniformity and performance of subsequent MOF.
[0123] Example 4
[0124] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is as follows:
[0125] (1) Prepare raw materials:
[0126] water;
[0127] Fe2(SO4)3;
[0128] Polyphenols: dopamine;
[0129] Phosphorus-containing flame retardant: ethylenediaminetetramethylenephosphonic acid;
[0130] Cellulose fiber fabric: Lyocell fiber fabric;
[0131] (2) Prepare the impregnation solution:
[0132] The Fe2(SO4)3, polyphenol, phosphorus-containing flame retardant and water are uniformly mixed and the pH of the system is adjusted to 4 to obtain an impregnation solution containing metal ions, polyphenol and phosphorus-containing flame retardant;
[0133] In the impregnation solution, the concentration of metal ions is 1.2 g / L, the concentration of polyphenols is 4 g / L, and the concentration of phosphorus-containing flame retardants is 2 g / L;
[0134] (3) Soaking and baking:
[0135] The cellulose fiber fabric was immersed in the impregnation solution at 45°C for 30 minutes, and then the excess water on the surface of the cellulose fiber fabric was removed, and the cellulose fiber fabric was baked at 105°C for 35 minutes to obtain a cellulose fiber fabric with MOF on the surface.
[0136] The mass ratio of the cellulose fiber fabric to the impregnation liquid is 1:18, and after removing excess water on the surface of the cellulose fiber fabric, the mass of the residual water in the cellulose fiber fabric is 75% of the mass of the cellulose fiber fabric.
[0137] The MOF of the cellulose fiber fabric containing MOF on the surface finally obtained is a regular cubic structure. The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is 29.2%, the thermal decomposition temperature is 286°C, the water contact angle is 165°, the water adhesion value is 27.63μN, and the water permeability is 2314g / (m 2 ·day), air permeability is 163m 3 / (m 2 h), the wear loss is 8.4g / 100cm 2 The wear cycle number is 3600, the longitudinal tear strength is 32N, the transverse tear strength is 33N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate is 12%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate is 24%. After 50 times of water washing, the change rate of each index does not exceed 10%.
[0138] Example 5
[0139] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is as follows:
[0140] (1) Prepare raw materials:
[0141] water;
[0142] Cu(NO3)2;
[0143] Polyphenols: Caffeic acid;
[0144] Phosphorus-containing flame retardant: ethylenediaminetetramethylenephosphonic acid;
[0145] Cellulose fiber fabric: Tencel fiber fabric;
[0146] (2) Prepare the impregnation solution:
[0147] The Cu(NO3)2, polyphenol, phosphorus-containing flame retardant and water are uniformly mixed and the pH of the system is adjusted to 6 to obtain an impregnation solution containing metal ions, polyphenol and phosphorus-containing flame retardant;
[0148] In the impregnation solution, the concentration of metal ions is 1.5 g / L, the concentration of polyphenols is 5 g / L, and the concentration of phosphorus-containing flame retardants is 3 g / L;
[0149] (3) Soaking and baking:
[0150] The cellulose fiber fabric was immersed in the impregnation solution at 60°C for 60 minutes, and then the excess water on the surface of the cellulose fiber fabric was removed, and the cellulose fiber fabric was baked at 130°C for 60 minutes to obtain a cellulose fiber fabric with MOF on the surface;
[0151] The mass ratio of the cellulose fiber fabric to the impregnation liquid is 1:20, and after removing excess water on the surface of the cellulose fiber fabric, the mass of the residual water in the cellulose fiber fabric is 75% of the mass of the cellulose fiber fabric.
[0152] The MOF of the cellulose fiber fabric containing MOF on the surface finally obtained is a regular cubic structure. The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is 29.5%, the thermal decomposition temperature is 288°C, the water contact angle is 163°, the water adhesion value is 27.91μN, and the water permeability is 2297g / (m 2 ·day), air permeability is 154m 3 / (m 2 h), the wear loss is 9.1g / 100cm 2 The wear cycle number is 3900, the longitudinal tear strength is 33N, the transverse tear strength is 33N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate is 13%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate is 23%. After 50 times of water washing, the change rate of each index does not exceed 10%.
[0153] Example 6
[0154] The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric is basically the same as that of Example 5, except that the impregnation solution configured in step (2) of this example also contains hydrogen peroxide at a concentration of 0.05 g / L.
[0155] The MOF of the cellulose fiber fabric containing MOF on the surface is a regular cubic structure. The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is 30.1%, the thermal decomposition temperature is 320°C, the water contact angle is 167°, the water adhesion value is 27.61μN, and the moisture permeability is 2200g / (m 2 ·day), air permeability is 150m 3 / (m 2 h), abrasion loss is 10g / 100cm 2The wear cycle number is 3700, the longitudinal tear strength is 32N, the transverse tear strength is 31N, and the irradiation intensity is 0.35W / m 2 After 500 hours of ultraviolet irradiation, the strength decrease rate is 14%. After 72 hours of exposure at a temperature of 70°C and a relative humidity of 90%, the tensile strength decrease rate is 24%. After 50 times of water washing, the change rate of each index does not exceed 10%.
Claims
1. A one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric, characterized in that: After immersing the cellulose fiber fabric in a solution containing metal ions, polyphenols and a phosphorus-containing flame retardant, removing excess water from the surface of the cellulose fiber fabric, and baking, a cellulose fiber fabric containing MOF on the surface is obtained; Phosphorus-containing flame retardants have amino and / or hydroxyl groups; The metal ion is Cu2+, and the pH value of the solution containing the metal ion, polyphenol and phosphorus-containing flame retardant is 4-6; Alternatively, the metal ion is Fe3+, and the pH value of the solution containing the metal ion, the polyphenol and the phosphorus-containing flame retardant is 2-4; In a solution containing metal ions, polyphenols and phosphorus-containing flame retardants, the concentration of metal ions is not less than 0.1 g / L, and the concentration of polyphenols is not less than 1 g / L; The immersion temperature is not less than 40℃; The immersion time should not be less than 20 minutes.
2. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 1, characterized in that: In the solution containing metal ions, polyphenols and phosphorus-containing flame retardants, the concentration of metal ions is not higher than 1.5 g / L, the concentration of polyphenols is not higher than 5 g / L, and the concentration of phosphorus-containing flame retardants is 0.5-3 g / L.
3. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 2, characterized in that: The solution containing metal ions, polyphenols and phosphorus-containing flame retardants also contains hydrogen peroxide, and the concentration of hydrogen peroxide is not higher than 0.1 g / L.
4. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 2, characterized in that: The mass ratio of the cellulose fiber fabric to the solution containing metal ions, polyphenols and phosphorus-containing flame retardant is 1:10-20.
5. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 1, characterized in that: The immersion temperature is not higher than 60°C.
6. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 1, characterized in that: The immersion time is not more than 60 minutes.
7. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 1, characterized in that: After removing excess water on the surface of the cellulose fiber fabric, the mass of the residual water in the cellulose fiber fabric is 60-80% of the mass of the cellulose fiber fabric.
8. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 1, characterized in that: The baking temperature is 100-130℃.
9. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to claim 1, characterized in that: The baking time is 30-60min.
10. The one-step method for in-situ construction of MOF on the surface of cellulose fiber fabric according to any one of claims 1 to 9, characterized in that: The MOF on the cellulose fiber fabric containing MOF on the surface is a regular cubic structure; The limiting oxygen index of the cellulose fiber fabric containing MOF on the surface is ≥28%, and the thermal decomposition temperature is 250-320°C; The water contact angle of the cellulose fiber fabric containing MOF on the surface is ≥160°, and the water adhesion value is ≤28.49μN; The moisture permeability of cellulose fiber fabric containing MOF on the surface is ≥2200g / (m 2 ·day), air permeability ≥150m 3 / (m 2 h); The abrasion loss of cellulose fiber fabric containing MOF on the surface is ≤10g / 100cm 2 The wear cycle number is more than 3500 times, the longitudinal tear strength and transverse tear strength are both ≥30N, and the irradiation intensity is 0.35W / m 2 The strength decrease rate is ≤15% after 500h of ultraviolet irradiation, and the tensile strength decrease rate is ≤25% after 72h of exposure at 70℃ and 90% relative humidity; After 50 washes, the change rate of each index of the cellulose fiber fabric containing MOF on the surface does not exceed 10%.
Citation Information
Patent Citations
Preparation method of formaldehyde-free washing-resistant flame-retardant fabric
CN110172823A
Recycled mask, preparation method and recycling method
CN112641147A
Super-hydrophobic and antibacterial natural cellulose fabric and preparation method thereof
CN112900102A
Water-soluble phosphazene antibacterial flame retardant, flame-retardant antibacterial fiber, flame-retardant antibacterial fiber fabric and preparation method of flame-retardant antibacterial fiber fabric
CN116289199A
Preparation method of hybrid iron-based metal organic framework nanofiltration membrane
CN117861442A